Nowe stanowiska derenia rozłogowego Cornus sericea L. w otulinie rezerwatu przyrody Skarpa Ursynowska w Warszawie - Zaniewska, Ewa; Kwaśny, Łukasz (Leśne Prace Badawcze, 2022)
Red osier dogwood Cornus sericea L. is a species native to North America, but spreading in Europe. It has been classified a kenophyte in Poland and is considered invasive. However, knowledge on its distribution is insufficient and lacking entirely for many parts of the country. Therefore, the aims of this study were to document stands of C. sericea in the buffer zone of the Skarpa Ursynowska nature reserve in Warsaw, to provide new information on morphological features that were inconsistently reported in the literature, and to summarise the known distribution of this species in the mazovian voivodeship. Field studies were carried out in 2021 within six new stands of C. sericea located in the buffer zone of Skarpa Ursynowska. The work included phytosociological relevés and measurement of the following parameters: length of leaves (blade and petiole) and the maximum height of plants. Based on the herb layer species found in the phytosociological relevés, ecological indicator values were calculated in order to determine habitat conditions. The distribution of the species in the mazovian voivodeship was then mapped by means of the ATPOL cartogram method. In the vicinity of the Skarpa Ursynowska, C. sericea occurred in scrub communities and at the early successional stages of forest development that is in habitats with favourable light conditions, sufficient humidity and fertility. The presence of a number of additional alien species was also a characteristic feature of the stands. C. sericea individuals identified in this survey were tall and showed almost no tendency to creep, most likely due to the favourable light conditions. Their leaves were larger (average length 189.2 mm) compared to published data, but the shape of the seeds was characteristic for the species. This is the first report of spontaneous occurrence of this species in Warsaw. The largest known concentration of C. sericea stands in the mazovian voivodeship was documented west of Warsaw and includes the Kampinos National Park. However, the small number of existing reports indicates that documentation of this species’ distribution in the region is still insufficient.